DESCRIPTIONS OF EMOTIONAL STRESS AND CHARACTERISTICS OF INFLUENCE OF STRESS ON THE PHYSICAL AND TECHNICAL PREPARATION OF FOOTBALL PLAYERS: DESCRIPTIONS OF EMOTIONAL STRESS AND CHARACTERISTICS OF INFLUENCE OF STRESS ON THE PHYSICAL AND TECHNICAL PREPARATION OF FOOTBALL PLAYERS - Hasanov, Anvar (Физическое воспитание, спорт и здоровье, 2025)
The article deals with the problem of the negative impact of stress on the athlete's competitive performance. Based on the theoretical analysis of literature data, the content of the concept of "stress" is determined, the internal and external stress factors of sports activities are specified and their manifestations, training of athletes with willpower to form resistance to stress, self-esteem it is recommended to increase the value, develop creative abilities and use various methods of mental self-management.